Diagnóstico de la fertilidad del suelo en áreas cultivadas de la ESPAM-MFL - Montesdeoca Villavicencio, María Concepción (2016)
The research was conducted at the Agricultural Polytechnic College of Manuel Félix Lopez campus, which aim was to diagnose soil fertility in cultivated areas of ESPAM-MFL, the experimental areas has 103 ha space, of which 60.58 ha (divided into 16 zones) are under agricultural production. Physical properties (texture, bulk density and soil drainage) were determined; chemical properties (nitrogen from organic matter , phosphorus , salinity , pH and exchangeable bases (calcium, magnesium, sodium and potassium) and organic matter, for the determination of physical variables 16 pits were performed, one in each study area, soils of cultivated areas of ESPAM-MFL presented loamy, indicating that possesses favorable characteristics for agricultural production, the agrochemical sampling was conducted to evaluate the chemical variables and consisted of taking twenty single samples to form a sample composed in each areas, all areas evaluated presented low and middle levels of N, P and exchangeable bases, so it should be made soil conservation practices via amendments.